Freedom from toxic relationships : moving on from the family, work, and relationship issues that bring you down - Carruthers, Avril (Tarcher/Penguin, 2013)
"Toxic relationships often come disguised as seemingly normal ones. These subtly destructive relationships are characterized by the slow erosion of self-esteem, a loss of personal identity, or a growing desire to please friends, partners, and family members who are impossible to please. In this uplifting and informative book, transpersonal psychotherapist Avril Carruthers will take a close look at adult relationships to show why we get involved in toxic relationships in the first place, and instruct the reader on how to recognize if they're involved in one"--